Microbiological Quality of Fresh-Cut Carrots and Process Waters - Määttä, Jenni; Lehto, Marja; Kuisma, Risto; Kymäläinen, Hanna-Riitta; Mäki, Maarit (International Association For Food Protection, 2013)
Fresh vegetables may be contaminated by pathogens in different ways after harvest. Pathogenic microorganisms associated with fresh vegetables can cause severe outbreaks of foodborne disease. We discuss here the results of microbiological analysis of carrot samples, as well as of washing, processing, and wastewater samples. Washed, unpeeled carrots generally contained the highest aerobic plate counts (mean, 5.5 log CFU/g). Escherichia coli was not detected in any carrot or water sample examined. The amounts of coliform bacteria and enterobacteria were higher in carrot samples taken from the first steps in the processing line than in samples taken in later phases of the process. Yersinia pseudotuberculosis was not detected in any of the samples by the cultivation method; however, nonpathogenic Yersinia enterocolitica was detected from most carrot samples and almost all washing water and wastewater samples but only from 2 of 10 process water samples. Using a more-sensitive real-time PCR method, pathogenic Y. enterocolitica was found from several carrot samples, and when these positive samples were cultivated, no pathogenic Y. enterocolitica strains were detected.
Keywords: Elintarvikkeet, ravitsemus; vihannekset; elintarvikehygienia; food hygiene; vegetable products